Konflik sosial dalam film BAC Nord karya Cédric Jimenez - Raditya, Andika; Tri Widyastuti, Wahyu; Asnidar, Yusi (Franconesia, 2022)
This research aims to explain the types of social conflicts contained in the film BAC Nord by Cédric Jimenez. The main theories used as a reference are two types of social conflict according to the theory of social conflict proposed by Lewis Coser (2001: 49) which consists of Realistic Conflict & Non-Realistic Conflict. The research method used is a qualitative descriptive analysis method using data collection techniques, namely the listening method and the recording technique which refers to the theory proposed by Mahsun (in Muhammad 2014:217-218). The collected data was analyzed using data analysis techniques according to theory by Miles and Hubermen (in Hardani 2020: 163-173), namely data reduction, data presentation (data display), and drawing conclusions.The results of this research on types of social conflicts according to the theory of Lewis Coser found in the film BAC Nord by Cédric Jimenez, there are thirty (30) data in the form of dialogue or conversation that indicate the existence of types of social conflicts. In detail, out of the thirty (30) dialogues, thirteen (13) dialogues were obtained that showed the existence of a type of realistic conflict social conflict. Furthermore, there are seventeen (17) dialogues that indicate the existence of a type of Non-Realistic Conflict social conflict.